On the phenomenon of impact - Kalapis Stephan (EDP Sciences, 2021)
Aerostructures such as plates are commonly used in aircraft structures due to their advantageous weight to stiffness ratio. Plates are susceptible to lateral forces that occur during impact. Such impact events are caused by falling tools, bird strikes, collisions of objects, and more. Several researchers have studied impact events, but not yet the behaviour of the plate and impactor shortly after impact due to various factors. In this paper, the semi-analytical approach of Karas is used to calculate key parameters for the analysis of an impact. Karas derived this approach to calculate an impact for a simply supported plate that is impacted in the center. Here, this approach is extended to calculate the impact event at any location on the plate. The linear semi-analytical approach is written in a Python script to obtain fast results. In a code-to-code analysis, this Python code is verified with a commercial FE solver. Various parameters are varied and investigated to analyze and describe the impact phenomenon. In addition to the influence of the initial velocity of the impactor, the mass ratio of the two bodies and the impact location are also investigated. The analysis shows that the contact force and maximum displacement during an impact varies depending on the impact location, while all other parameters are kept constant. Depending on the impact location, the contact force between impactor and plate can be nine times higher than the lowest value.